THE EFFECT OF MATHEMATICAL LOGICAL INTELLIGENCE ON PROBLEM SOLVING ABILITY IN COMPLETION OF STORY QUESTIONS - Puji Astuti; M. Saidun Anwar; Choirudin; Apri Wahyudi; Rani Darmayanti (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The phenomenon that often occurs in the process of learning mathematics is that students are less able to understand the concept of a series of stories, relate one mathematical concept to another, and have not been able to formulate it with logical, systematic and critical thinking. So it can be said that students' mathematical ability is still relatively low. The aims of this study to describe the mathematical logical intelligence of the students SDN 01 Bumi Pratama Mandira. This study uses a quantitative approach to the type of research ex post facto. The population in this study were 25 students SDN 01 Bumi Pratama Mandira. The sample in this study consisted of 25 students taken from the population using a random method. Data collection techniques using questionnaires, and test questions. The data analysis technique used is Simple Linear Regression. The results of this study indicate that based on the results of the analysis above, it shows that there is a positive and significant influence of mathematical logical intelligence on problem solving abilities in solving story problems. Then the contribution of logical-mathematical intelligence affects problem-solving ability, by 68.6% while the remaining 31.4% is influenced by other variables.